Industry 4.0 and Sustainability: A Systematic Review on Advanced Technologies and Collaborative Models - Patrício, Leonel; Varela, Leonilde (EAI Endorsed Transactions on Digital Transformation of Industrial Processes, 2026)
INTRODUCTION: Industry 4.0 (I4.0) technologies demonstrate strong potential to enhance sustainable industrial practices; however, their holistic and integrated application across sustainability dimensions remains insufficiently explored in the literature. OBJECTIVES: This paper aims to analyse how Industry 4.0 technologies contribute to sustainability across environmental, economic, and social dimensions, identifying dominant technologies, sectoral adoption patterns, existing gaps, and alignment with the United Nations Sustainable Development Goals (SDGs). METHODS: A systematic literature review of 32 peer-reviewed articles published between 2015 and 2025 was conducted using the PRISMA framework. The study combines bibliometric analysis with qualitative content analysis to assess technological contributions, sectoral applications, and sustainability outcomes. RESULTS: The results show that IoT and Artificial Intelligence are the most frequently adopted I4.0 technologies, predominantly contributing to environmental (78% of studies) and economic sustainability. Social sustainability remains underrepresented, appearing in only 25% of the analysed studies. Manufacturing and energy sectors lead adoption, while agri-food and construction sectors lag despite their high potential. Major challenges include data privacy risks associated with IoT and scalability limitations of Blockchain technologies, with mitigation strategies focusing mainly on SME-oriented adoption models. CONCLUSION: The findings highlight the need for a more balanced deployment of Industry 4.0 technologies that equally addresses environmental, economic, and social dimensions of sustainability. Future research should prioritize the development of measurable social impact indicators and integrated technological–policy frameworks to support inclusive and sustainable industrial transformation aligned with the UN SDGs.